Trichomonas vaginalis extracellular vesicles suppress IFNε-mediated responses driven by its intracellular bacterial symbiont Mycoplasma hominis - Joshua A. Kochanowsky; Emma L. Betts; Gabriel Encinas; Johnson Amoah; Patricia J. Johnson (Proceedings of the National Academy of Sciences, 2025)
Trichomonas vaginalis is a common, extracellular, sexually transmitted parasite which is often found in symbiosis with the intracellular bacterium Mycoplasma hominis (Mh), an opportunistic pathogen of the female reproductive tract. How this symbiosis affects infection outcomes and the host cell innate immune response is poorly understood. Here, we show that infection with T. vaginalis in symbiosis with M. hominis or M. hominis alone triggers a noncanonical type I interferon, interferon-epsilon (IFNε), but infection with T. vaginalis alone does not. We also demonstrate that extracellular vesicles (TvEVs) produced by the parasite downregulate host cell IFNε, counteracting this symbiont-driven response and elevating infection. We further demonstrate that IFNε, a hormonally regulated cytokine produced in the human reproductive system, is protective against T. vaginalis cytoadherence and cytolysis of host cells. These studies provide insight into how a parasite and its bacterial symbiont work in concert to regulate host cell innate immune responses to drive infection.